2022
DOI: 10.3390/plants11070922
|View full text |Cite
|
Sign up to set email alerts
|

Drought Stress Responses: Coping Strategy and Resistance

Abstract: Plants’ resistance to stress factors is a complex trait that is a result of changes at the molecular, metabolic, and physiological levels. The plant resistance strategy means the ability to survive, recover, and reproduce under adverse conditions. Harmful environmental factors affect the state of stress in plant tissues, which creates a signal triggering metabolic events responsible for resistance, including avoidance and/or tolerance mechanisms. Unfortunately, the term ‘stress resistance’ is often used in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 114 publications
(204 reference statements)
2
48
0
Order By: Relevance
“…The underground part of the plant (the root system), in addition to providing a site for fixation and water and nutrient uptake, plays a significant role in evolving abiotic stress responses [17,53]. Prolonged drought can induce adaptive responses in plants, and it can be manifested by modified structure and function of roots [53], which can play an important role in coping with water stress [19,35,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underground part of the plant (the root system), in addition to providing a site for fixation and water and nutrient uptake, plays a significant role in evolving abiotic stress responses [17,53]. Prolonged drought can induce adaptive responses in plants, and it can be manifested by modified structure and function of roots [53], which can play an important role in coping with water stress [19,35,55].…”
Section: Discussionmentioning
confidence: 99%
“…This fact suggests that there may be large differences between species and cultivars in drought stress responses, and even variability has been found in the susceptibility of potato cultivars [15,16]. Several experiments were performed to identify traits that could be related to drought stress and to select genotypes with the desired characters in several crops [4,17] including potatoes [18][19][20]. Some of these traits can also be detected at the cellular and/or tissue level, such as the adjustment of osmotic pressure, which can be tested/modelled under laboratory conditions [21] or even in vitro [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Drought stress (DS) is the worst environmental factor around the globe and severely affects crop yield ( Anjum et al, 2011 ; Alharby and Fahad, 2020 ; Seleiman et al, 2021 ; Yahaya and Shimelis, 2022 ). DS is an inevitable abiotic aspect in numerous ecological areas, severely declining crop yield and quality without warning before its onset ( Seleiman et al, 2021 ; Bandurska, 2022 ). Low rainfall, temperature, and light intensity contribute to drought incidents ( Zia et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tree photosynthesis is very sensitive to water deficit [26,27], which directly affects fruit development and final yield [13,28]. To reduce water loss during periods of drought, plants often first down-regulate stomatal conductance (gs) and then may increase osmotic adjustments to facilitate water absorption in drier soils [29][30][31][32][33]. For example, studies on pear-jujube (Zizyphus jujuba M. cv.…”
Section: Introductionmentioning
confidence: 99%
“…Chemlali) showed that water deficit decreased leaf net photosynthetic rate (Pn) slightly but significantly reduced the transpiration rate (Tr), thus resulting in significant improvements in leaf water use efficiency and indicating that fruit trees can adapt to a certain degree of water stress by controlling stomatal aperture [13,34,35]. Prolonged drought has significant negative impacts on the uptake, transport and metabolism of various nutrients, minimizing leaf area, altering the partitioning of assimilates among different plant organs and reducing yield [29,36]. However, the extent to which fruit trees can adjust and acclimate to drought, increasing water use efficiency to save water and maintain steady yield, varies with species.…”
Section: Introductionmentioning
confidence: 99%